Divergent Responses of Floral Traits of Lonicera nervosa to Altitudinal Gradients at the Eastern Margin of Hengduan Mountains - Chen, Wenkai; Wang, Lihua; Wang, Jinniu; Joshi, Srijana; Xiang, Shuang; Tariq, Akash; Liu, Xiaodan; Liao, Yuchen; Wu, Yan (Frontiers in Ecology and Evolution, 2021)
Understanding phenotypic responses is crucial for predicting and managing the effects of environmental change on native species. Color and display size are typically used to evaluate the utilization value of ornamental plants, which are also important ornamental characters of Lonicera nervosa Maxim. (L. nervosa). However, there is limited documentation of its floral environmental adaptation. The environmental conditions for the development of an organism changes with altitudinal variation. The aim of this research was to find flower traits variability maintenance and the trade-off amongst the organs in five different populations of L. nervosa growing at distinct altitudes. We investigated the distribution patterns of floral color, floral display and biomass tradeoff along a 700-m altitude gradient from 2950 to 3650 m. One-way ANOVA analysis was performed to assess the variability of flower traits and floral color across different altitudes. Moreover, correlations and tradeoffs between flowers and vegetative organs were also observed at different altitude ranges. The results indicated that L. nervosa flowers had strong adaptability along the elevation and divergent altitude-range-specific patterns, which was divided by an altitude breakpoint at around 3300 m. Below 3300 m, petal lightness (petal L) decreased but total floral display area (TFDA), individual floral dry mass (IFDM) and total floral dry mass (TFDM) increased with increase in altitude. Whereas above 3300 m, no significant difference was observed in petal L, while TFDA, IFDM and TFDM decreased slightly with increase in altitude. The responsibility for the selection on floral color at lower altitude was stronger than that at higher altitude, while the selection agents on floral biomass had significant effects within the entire altitude range. However, the effects on floral biomass were opposite on both sides of 3300 m. Thus, floral trait and floral color can be useful indicators for domestication of horticultural plants and help to evaluate and initiate management and conservation actions.